2011
DOI: 10.4028/www.scientific.net/amr.255-260.2761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perforation Pollution Zone on Fracture Initiation

Abstract: Fracture initiation is a key factor of hydraulic fracturing, as lack of research on fracture initiation position.The perforation geostress mechanical model of low permeability reservoir is built according to the rock mechanics, seepage mechanics, elastic-plastic mechanics, considering solid-fluid coupling and rock material nonlinearity. Adopting the transient analysis, low-permeability reservoir geostress distribution of different stages is obtained using the finite element, such as drilling - cementing - perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The perforation geostress mechanical model was investigated by Wang et al [11]. Their research demonstrated that lowpermeability reservoir geostress distribution of different stages determined the fracture initiation position and fracture pressure, taking into account the rock failure criterion.…”
Section: Introductionmentioning
confidence: 99%
“…The perforation geostress mechanical model was investigated by Wang et al [11]. Their research demonstrated that lowpermeability reservoir geostress distribution of different stages determined the fracture initiation position and fracture pressure, taking into account the rock failure criterion.…”
Section: Introductionmentioning
confidence: 99%